EKSPLORASI NILAI-NILAI KONSELING DALAM PERMAINAN TRADISIONAL GOBAK SODOR DI KABUPATEN BONDOWOSO - Mohamad Fadil; Samsul Arifin; Abd. Mughni (Konseling At-Tawazun, 2024)
The gobak sodor game is a game played in groups, where the group of guards tries to block the attacking group when they want to pass through the game squares. The traditional game Gobak Sodor contains many positive values. The aim of this research is to explore the counseling values contained in the traditional game gobak sodor in Bondowoso Regency. This research uses qualitative research methods with an ethnographic type of research. From the research results, there are counseling values in the traditional game of gobak sodor in Bondowoso Regency, namely: spirituality, kinship, honesty, cooperation, strategy setting, leadership, social care, physical and mental health.